A systematic literature review of meaning-oriented resilience as a coping process for pregnancy anxiety and maternal well-being - Nurul Jannah; Nisa Rachmah Nur Anganthi; Sri Lestari; Lisnawati Ruhaena (Science Midwifery, 2026)
Pregnancy involves profound physiological and psychosocial changes that increase vulnerability to stress and anxiety. Psychological resilience has been widely recognized as a protective factor for maternal mental health; however, existing research has largely emphasized functional outcomes, with limited attention to meaning-oriented coping processes underlying maternal adaptation. This systematic literature review aimed to synthesize empirical and conceptual evidence on meaning-oriented resilience in relation to pregnancy anxiety and maternal well-being. Following PRISMA 2020 guidelines, systematic searches were conducted in Scopus and Google Scholar, yielding 26 eligible studies analyzed through theory-driven thematic synthesis. The findings indicate that psychological resilience operates as a dynamic coping process that reduces prenatal anxiety and supports emotional regulation and adjustment. Religious and spiritual coping consistently emerged as meaning-oriented mechanisms that strengthen resilience by enabling pregnant women to interpret pregnancy experiences within value-based and existential frameworks. Conceptual evidence suggests that ṣabr represents an active form of meaning-oriented resilience characterized by emotional regulation, endurance, and value-driven perseverance. While most studies focused on symptom reduction, emerging evidence highlights the role of resilience and spirituality in promoting holistic maternal well-being. This review advances a meaning-oriented framework of maternal resilience integrating psychological and Islamic perspectives and supports the incorporation of meaning-based and culturally sensitive approaches within midwifery care to enhance maternal mental health during pregnancy.